2011
DOI: 10.3892/ijmm.2011.811
|View full text |Cite
|
Sign up to set email alerts
|

ORAOV1 is a probable target within the 11q13.3 amplicon in lymph node metastases from gastric adenocarcinoma

Abstract: Abstract. The lymph node metastatic (LNM) spread of tumor cells is a frequent event in the initial process of cancer dissemination and is a powerful independent prognostic indicator in gastric adenocarcinoma (GAC). High density genomic arrays were conducted to identify molecular markers associated with lymph node metastasis in GAC. In the genome-wide profile, large copy number gains involving chromosomes 1p, 3q, 8q, 9q, 11q, 16p, 19p, and 20q (log 2 ratio >0.25) (>40% of patients) were more prevalent than copy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Amplification of the 11q13.3 region is one of the most common aberrations in multiple human cancers including ESCC and has been implicated with tumor malignancy. Many studies have demonstrated that 11q13.3 amplicon was positively correlated with LNM [ 1 , 19 21 , 46 ], however, despite the clinical relevance, the causal relationship and underlying molecular mechanisms of 11q13.3 amplicon involved in lymphatic metastasis are still unknown. In this study, by setting more rigorous criterions, we found that miR-548k, a microRNA located in the 11q13.3 amplicon, might execute the function of 11q13.3 amplicon to regulate lymphatic metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Amplification of the 11q13.3 region is one of the most common aberrations in multiple human cancers including ESCC and has been implicated with tumor malignancy. Many studies have demonstrated that 11q13.3 amplicon was positively correlated with LNM [ 1 , 19 21 , 46 ], however, despite the clinical relevance, the causal relationship and underlying molecular mechanisms of 11q13.3 amplicon involved in lymphatic metastasis are still unknown. In this study, by setting more rigorous criterions, we found that miR-548k, a microRNA located in the 11q13.3 amplicon, might execute the function of 11q13.3 amplicon to regulate lymphatic metastasis.…”
Section: Discussionmentioning
confidence: 99%